Selling Natural Laws: The Structure and Function of Naturism in early 1950s France - Bernard, Léo (Implicit Religion, 2024)
This article describes the French naturist milieu of the early 1950s. In line with the questions raised by this special issue, I focus on the commercial structures of naturism, such as the selling of natural products and foods and the renting of bungalows and camping pitches, and on its “guiding function,” namely the rationalization of the irrational through the use of the concept of natural laws and the injunctions stemming out these laws. Based on this case study, I invite the reader to rethink the categorizations of “religion” and “business” by considering what underpins them.